2008
DOI: 10.1016/j.jcrimjus.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Police criminal charging decisions: An examination of post-arrest decision-making

Abstract: Scholars have encouraged studies of police decision-making to move beyond the arrest decision into research that broadens the understanding of police behavior. The criminal charge placed by officers against offenders is largely an untouched area of study. Examining criminal charging decisions goes beyond simple dichotomous decisions, such as arrest, but instead explores the area of police leniency or punitiveness. Randomly constructed vignettes describing a domestic violence incident were given to officers fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
0
24
0
1
Order By: Relevance
“…Policing has been witness to a significant amount of problematic issues (Blackwell & Vaughn, 2003;Kowalski & Lundman, 2007;McElvain & Kposowa, 2004;Phillips & Varano, 2008;Weir, Stewart, & Morris, 2012;Weitzer, 2002;Zhao, Ren, & Lovrich, 2010) as well as innovation and change in recent years (Culver, 2004;Zhao, Lovrich, & Robinson, 2001). For example, regarding the latter, technology is transforming modern policing; it is enhancing crime fighting capabilities, police accountability, and police-community relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Policing has been witness to a significant amount of problematic issues (Blackwell & Vaughn, 2003;Kowalski & Lundman, 2007;McElvain & Kposowa, 2004;Phillips & Varano, 2008;Weir, Stewart, & Morris, 2012;Weitzer, 2002;Zhao, Ren, & Lovrich, 2010) as well as innovation and change in recent years (Culver, 2004;Zhao, Lovrich, & Robinson, 2001). For example, regarding the latter, technology is transforming modern policing; it is enhancing crime fighting capabilities, police accountability, and police-community relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Hence it has been argued that arrest rates are as much a reflection of local enforcement policies and attitudes and police experience as they are a reflection of criminal behavior (Phillips and Varano 2008). Similarly, convictions may reflect legal resources available to patients as well as judicial policies, not just the commission of a crime.…”
mentioning
confidence: 99%
“…Apparently this result is not uncommon. One study of officer charging decisions at domestic violence calls in New York found more than 50 % of officers applied multiple charges to argumentative suspected batterers, including charges of Bcriminal contempt^which is somewhat similar to disorderly conduct or obstruction of justice (Phillips and Varano 2008).…”
Section: Resultsmentioning
confidence: 99%
“…While the vignettes lacked sufficient probable cause to justify an arrest for any offense, the prosecutor indicated he had observed officers arrest on charges of disorderly conduct, even if unjustified, as a way to diffuse disputes or punish persons who challenged their authority. The policing literature has also provided examples of disorderly conduct arrests being utilized in this manner (Muir 1977;Phillips and Varano 2008;Skolnick 1966;Westley 1970). As a result, a second question was posed to the respondents that asked, BHow likely would you be to arrest the man for disorderly conduct?^The response choices again included very likely, somewhat likely, unsure, somewhat unlikely, and very unlikely.…”
Section: Instrumentationmentioning
confidence: 99%